In claris non fit interpretatio: the illusions of norvativism in hermeneutic criticism (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The ‘hermeneutic consciousness’ does not simply represent a set of prescriptiverules meant to generate a correct legal reasoning. It is indeed a philosophical conception,with deep logical and ontological implications, focused on showing thoseconditions that make legal experience intelligible.Such a peculiar conceptual richness requires, nevertheless, to assume two preconditions:a) a dialectic theory of argumentation at the base of the legal reasoning(fundamental in order to implement the ‘pars construens’ of the hermeneutic vision);b) a processualistic perspective, rather than the inadequate lens of normativism(whose limits will be shown thanks to typically hermeneutical argumentations).
Keywords: normativism; processualism; hermeneutics; syllogistical conception of judicial decisions; dialectial procedure; legal illuminism; interpretation; legal language; legal certainty.